Regional income convergence and inequality in boom and bust. Results from micro data in Finland 1971-2000, and especially during the 1990s - Loikkanen, Heikki; Riihelä, Marja; Sullström, Risto (Louvain-la-Neuve: European Regional Science Association (ERSA), 2003)
We use micro (Household Survey and Income Distribution Statistics) data to study income differences both between and within four major regions (Helsinki region, Southern, Middle and Northern Finland) during 1971-2000. The former is related to regional income convergence vs. divergence and the latter to inequality at national level and within regions. Besides long-term developments, we are interested in what happened during boom-bust-boom period that began in late 1980s. It included besides economic turmoil also institutional changes ranging from financial liberalization, tax reforms to EU and EMU membership. Also the structure of the economy changed with the rise of IT industry. Micro data based (factor, gross and disposable) income measures indicate that there has been convergence among Finnish regions over time, more earlier and less when we come closer to the end of 1980s. Regional disparities remained more or less the same also in the depression of early 1990s, and increased only slightly in the subsequent boom. As for inequality, the greatest decline in (disposable) income differences since 1971 took place before mid-1980s, thereafter inequality remained pretty much at the same level. Somewhat surprisingly, this was also the case in early 1990s, when output dropped and unemployment increased dramatically. When the recovery began in mid-1990s inequality began to increase rapidly. These developments were surprisingly similar both at national level and at the level of major regions thinking of both time profiles and levels of most typical inequality indicators (Gini coefficients, generalised entropy measures). Only in the recovery period we could detect clear regional divergences as inequality in the Helsinki Region began to increase earlier and to greater extent than elsewhere. Our results also indicate that the Welfare State (transfers and taxation) decreases regional disparities and inequality. We also consider poverty to supplement our analysis of inequality.